Maya Manual - Lavender, Dan. (Springer Professional Computing, 2003)
Alias|Wavefront's Maya 3D animation software is an integrated collection of tools for creating computer generated images, used in nearly every blockbuster special effects film that has been released in the last few years. The first choice for digital content creators, Maya combines animation, dynamics, modelling and rendering tools, enabling you to create digital characters and visual effects for live action films or stand-alone animation. Key Topics Using plenty of examples and illustrations to provide insights into the functioning and context of Maya, Dan Lavender explains how to: * understand the framework fundamentals of Maya; * create 3D objects; * work with models and surfaces; * animate objects; * use colours, lighting and rendering. About the Author Dan Lavender is a Technical Director at Framestore CFC - one of Europe's largest post-production companies. Features and Benefits * Gives a broad overview of Maya, enabling you to create your own high quality 3D computer generated images - even if you have never used a 3D package before. * The source files and scenes to accompany the examples in the book are available from the Springer web site - springer.co.uk/mayamanual.